Cross-cultural effects of COVID-19 on higher education learning and teaching practice: A case study from Greece - Kefalaki, Margarita; Nevradakis, Michael; Li, Qing (Journal of University Teaching and Learning Practice, 2021)
COVID-19 has greatly impacted all aspects of our everyday lives. A global pandemic of this magnitude, even as we now emerge from strict measures such as lockdowns and await the potential for a ‘new tomorrow’ with the arrival of vaccines, will certainly have long-lasting consequences. We will have to adapt and learn to live in a different way. Accordingly, teaching and learning have also been greatly impacted. Changes to academic curricula have had tremendous cross-cultural effects on higher education students. This study will investigate, by way of focus groups comprised of students studying at Greek universities during the pandemic, the cross-cultural effects that this ‘global experience’ has had on higher education, and particularly on students in Greek universities. The data collection tools are interviews and observations gathered from focus groups. Keywords: Cross-cultural effects; COVID-19; international students; higher education teaching and learning; global education; higher education; online education.